Apitherapy applied to the treatment of onychomycosis: a critical review of the literature on propolis (Research, Society and Development, 2022)
Onychomycosis is a nail infection caused by fungi, affects about 5.5% of the world population, and is more frequent in individuals over 60. The agents of infection are dermatophyte fungi (60% to 70%), non-dermatophyte filamentous fungi and yeast (together they add up to 30% to 40%). Treatment includes topical or oral antifungal drugs, and treatment time ranges from three months to more than a year. Alternative therapies are used empirically based on popular culture. The aim of this study was to review the literature on the use and effectiveness of propolis and its derivatives in the treatment of nail mycosis. For this, virtual libraries, search sites and databases were used: Scielo, Pubmed and Portal Periodicals of CAPES, including publications until February 2022. The search words (in Portuguese and in their respective versions in English) were: (“onychomycosis” OR “tinea unguium” OR “nail mycosis”) AND (“treatment” OR “therapy”) AND (“propolis”). Eight articles were included in this study, and the majority (five) evaluated the activity of propolis in vitro on fungal agents of nail mycosis, two studies simultaneously evaluated propolis in the treatment of onychomycosis in vivo, in vitro and ex vivo and one study analyzed the in vivo treatment. Thus, it was found that propolis has antifungal activity and can be considered as a complementary or alternative therapy for the treatment of onychomycosis.